UJI DAYA TERIMA DAN NILAI GIZI BISKUIT YANG DIMODIFIKASI DENGAN TEPUNG UMBI DAHLIA(Dahlia Sp) - Yolanisa Harahap; Fitri Ardiani; Evawany Y Aritonang (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Dahlia tuber is a plant that source of inulin and has a function as a prebiotic that is good for the digestive system, but its use as a food are rare. One form of the use of dahlia tuber by processed into flour and used in making biscuit. The purpose of this research was aimed to determine the acceptability and nutrient content from a biscuit with addition of dahlia tuber flour. This study is an experimental study with two treatment that is biscuit with addition of dahlia tuber flour by 25% and 50%. Acceptability test of biscuit with addition of dahlia tuber flour was given to thirty panelist of students in Faculty of Public Health University of North Sumatera. Analysis carbohydrate content were tested in the laboratory of Industrial Research and Standardization Agency Medan and inulin content were tested in laboratory of PT. Saraswanti Indo Genetech Bogor. The results showed that organoleptic test based on flavor, aroma, color, and texture, the most preferred biscuit by panelists are biscuit with addition of dahlia tuber flour by 25%. The addition of dahlia tuber flour in biscuits making increased the content of carbohydrate and inulin. The addition of dahlia tuber flour with different concentrations gave a significantly different effect on the flavor and aroma but does not give a different effect on color and texture of biscuit. It is suggested for people be able to make dahlia tuber biscuits as a snack food because it contains carbohydrate and inulin that required for body and beneficial for health. It also suggested to do other foods diversification from dahlia tuber as a food which is rich in nutrient content. Keyword: Biscuit, Dahlia Tuber, Acceptability Test, Inulin